Recreational marijuana laws and the misuse of prescription opioids: Evidence from National Survey on Drug Use and Health microdata. (5th November 2022) - Ali, Mir M.; McClellan, Chandler; Mutter, Ryan; Rees, Daniel I.
Abstract: Several studies have concluded that legalizing medical marijuana can reduce deaths from opioid overdoses. Drawing on micro data from the National Survey on Drug Use and Health, a survey uniquely suited to assessing patterns of substance use, we examine the relationship between recreational marijuana laws (RMLs) and the misuse of prescription opioids. Using a standard difference‐in‐differences (DD) regression model, we find that RML adoption reduces the likelihood of frequently misusing prescription opioids such as OxyContin, Percocet, and Vicodin. However, using a two‐stage procedure designed to account for staggered treatment and dynamic effects, the DD estimate of relationship between RML adoption and the likelihood of frequently misusing prescription opioids becomes positive. Although event study estimates suggest that RML adoption leads to a decrease in the frequency of prescription opioid abuse, this effect appears to dissipate after only 2 or 3 years.